Conducting a Community Forum to Address Youth Substance Abuse - Emily Rickerson; Muthusami Kumaran; Kate Fogarty (EDIS)
Community forums are about participatory democracy at a local level. They involve gathering citizens of a community together to discuss issues, make choices on how to deal with them, and develop common ground to resolve those issues. This 4-page fact sheet provides suggestions for leading and conducting a forum on youth substance abuse, based on the National Issues Forums (NIF) model. Written by Emily Rickerson, Muthusami Kumaran, and Kate Fogarty, and published by the UF Department of Family Youth and Community Sciences, August 2011. (Photo ©Grand Rapids, MI)